High school students' feelings: Discoveries from a large national survey and an experience sampling study. (April 2020) - Moeller, Julia; Brackett, Marc A.; Ivcevic, Zorana; White, Arielle E.
Abstract: We investigated students' feelings at high school in a nation-wide survey of 21, 678 US students (study 1), and in a four-week study using experience sampling methodology (ESM) with 472 students across 5 high schools (study 2). Both studies combined mixed methods, including open-ended questions and rating scales (e.g., PANAS). In study 1, seventy-five percent of the feelings students reported in their responses to open-ended questions were negative. The three most frequently mentioned feelings were tired, stressed, and bored. Similar findings emerged with rated items, The prevalence of negative feelings was largely similar across demographic groups. Study 2 largely corroborated the findings from study 1. Although the retrospective measures showed similar results to study 1, the in-the-moment measures also showed frequent positive feelings. We discuss the findings in light of the 'sleep deprivation epidemic', the achievement motivation literature, and implications for the validity of state- and trait measures of academic emotions. Highlights: High school students' feelings were studied in two US samples (N1 = 21, 678; N2 = 472). Methods included open-ended questions, rated items and Experience Sampling Method. 75% of all feelings students reported in their open-ended responses were negative. Feeling tired was the most prominent feeling, across measures and samples. Negative feelings about school prevailed across all demographic groups.